Ecosystem services as a tool for decision making in Patagonia - Peri, Pablo Luis; Nahuelhual, Laura; Martínez Pastur, Guillermo José (Springer, 2021)
The Patagonia region that lies within two countries (12% in Chile and 88% in Argentina) has some of the most extensive wilderness areas in the planet (forests, shrublands, grasslands, and wetlands), as well as many low affected coastal-marine ecosystems. However, this “last frontier of capitalism” has started to experience the simultaneous expansion of the green and blue growth sectors, with unknown consequences for biodiversity, ecosystem services (ES) and livelihoods. In this chapter, we (i) present a conceptual framework for the sustainable management of the natural ecosystems in Patagonia that guides the chapters of this book and (ii) highlight the importance of the ES approach for better decision-making. Our conceptual framework starts from a non-dichotomous conception of the relationships between society and ecosystems. This determines a socio-ecosystem composed by a biophysical, economic-productive and socio-political-cultural sub-system. One major challenge in Patagonia is that ES are often unrecognized and undervalued and, therefore, ignored in market transactions, government policies and land and ocean management practices. In this context, this book aims to highlight the multiple ES provided by Patagonian ecosystems, their relation to ecosystems’ functioning, how they sustain human well-being and the threats they are subjected to.